Five‐year follow‐up of substantia nigra echogenicity in idiopathic REM sleep behavior disorder. Issue 14 (10th November 2014) - Iranzo, Alex; Stockner, Heike; Serradell, Mónica; Seppi, Klaus; Valldeoriola, Francesc; Frauscher, Birgit; Molinuevo, José Luis; Vilaseca, Isabel; Mitterling, Thomas; Gaig, Carles; Vilas, Dolores; Santamaria, Joan; et al.
Abstract Hyperechogenicity of the substantia nigra visualized by transcranial sonography occurs in most Parkinson's disease (PD) patients. Idiopathic rapid eye movement (REM) sleep behavior disorder (IRBD) subjects eventually develop PD and other synucleinopathies. This study was undertaken to evaluate whether in IRBD, transcranial sonography identifies subjects who convert to PD and other synucleinopathies, and whether substantia nigra echogenic size changes with time. It was a prospective study in which 55 IRBD patients underwent transcranial sonography at baseline and were invited to follow‐up after 5 years. Patients were assessed by the same experienced sonographer who was blinded to clinical data and baseline transcranial sonography results, and used the same equipment and adjustments. Twenty‐one (38.2%) subjects were diagnosed with a synucleinopathy (PD in 11, dementia with Lewy bodies in nine, and multiple system atrophy in one). Sensitivity of baseline substantia nigra hyperechogenicity for the development of a synucleinopathy was 42.1%, specificity 67.7%, positive predictive value 44.4%, negative predictive value 65.6%, and relative risk 1.29. No differences were detected between the first and second examination in mean size of the substantia nigra (0.20 ± 0.09 cm2 vs. 0.19 ± 0.07 cm2; P = 0.777) and in percentage of patients with substantia nigra hyperechogenicity (33.3% vs. 42.8%, P = 0.125). Transcranial sonography of the substantia nigra alone is not a useful tool to identify IRBD subjects at risk for the development of PD or a synucleinopathy after 5 years of follow‐up. In IRBD, transcranial sonography cannot be used to monitor the degenerative process in the substantia nigra, because echogenicity size remains stable over time. © 2014 International Parkinson and Movement Disorder Society